Evaluation Of Application Of Web Bases Budget Realization Report Seen From Human Computers Interaction Perspective - Afandi, Yosi; Pribadi, Joni Dwi (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2019)
The preparation of Budget realization report is a routine activity that must be done in the Department of Cominfo and Statistics. The use of budget realization applications has been implemented but there has been no evaluation of the application so that researchers evaluated the application with the purpose of improving the application in the future. The method used to evaluate is TAM, with the results of the research that the application of the budget Realization report on the basis is good but there are some things that need to be done application development in the ease of use and meaning of Symbols that exist in the system thus improving the quality of the system, the quality of information and service quality thereby affecting the use of a good budget realization application